Prevalence of Growth Restriction at Birth for Newborns With Congenital Heart Defects: A Population-Based Prospective Cohort Study EPICARD - Ali Ghanchi; Ali Ghanchi; Makan Rahshenas; Damien Bonnet; Damien Bonnet; Neil Derridj; Neil Derridj; Nathalie LeLong; Laurent J. Salomon; Laurent J. Salomon; Francois Goffinet; Francois Goffinet; et al. (Frontiers Media S.A., 2021)
Background and Objectives: Congenital heart defects (CHD) and growth restriction at birth are two major causes of childhood and adult morbidity and mortality. The aim of this study was to assess the overall risk of growth restriction at birth, as measured by its imperfect proxy small (< 10th percentile) for gestational age (SGA), for newborns with CHD.Methods: Using data from a population-based cohort of children born with CHD, we assessed the risk of growth restriction at birth using SGA and severe SGA (3rd percentile). To compare the odds of SGA and severe SGA across five specific major CHD, we used ordinal logistic regression using isolated, minor (non-operated) ventricular septal defect (VSD) as the control group.Results: The overall proportion of SGA for "isolated" CHD (i.e., those not associated with other anomalies) was 13% (95% CI, 12-15%), which is 30% higher than what would be expected in the general population (i.e., 10%). The risk of severe SGA was 5% (95% CI, 4-6%) as compared with the expected 3% in the general population. There were substantial differences in the risk of overall SGA and more so severe SGA across the different CHD. The highest risk of SGA occurred for Tetralogy of Fallot (adjusted OR 2.7, 95% CI, 1.3-5.8) and operated VSD (adjusted OR 2.1, 95% CI, 1.1-3.8) as compared with the control group of minor (non-operated) VSD.Conclusion: The overall risks of both SGA and severe SGA were higher in isolated CHD than what would be expected in the general population with substantial differences across the subtypes of CHD. These results may provide a clue for understanding the underlying mechanisms of the relation between alterations in fetal circulation associated with different types of CHD and their effects on fetal growth.